Influence of the Caldwell report, and other computer generated interpretive reports, in child custody evaluations: A brief report. Issue 4 (2nd October 2018) - Stolberg, Ronald A.
Abstract: This brief report reviews the use of MMPI-2 computer-generated interpretive reports in child custody evaluations. Particular attention was aimed at the Caldwell Report's MMPI-2 Custody Report. Considering the recent temporary closure of the Caldwell Report, this article will discuss what scoring and report options remain currently for interpretive custody reports. A perspective is shared that a dependence on computer-generated interpretive reports is detrimental to the science and practice of custody evaluation work. Finally, the author calls for future and revised computer-generated interpretive reports to include more information regarding a link to conclusions, gender bias, and peer reviewed research.